Not for the Faint of Heart: Assessing Physical Violence and Psychological Abuse against U.S. Mayors. (March 2019) - Thomas, Sue; Herrick, Rebekah; Franklin, Lori D.; Godwin, Marcia L.; Gnabasik, Eveline; Schroedel, Jean R.
Despite evidence of abuse and violence against U.S. elected officeholders at the federal, state, and local levels, to date, no political science research has investigated the frequency, channels, and correlates of this phenomenon. Here, we surveyed mayors in U.S. cities with populations above 30, 000 and found that mayors face physical violence and psychological abuse at rates equal to or greater than the general workforce, social media are the most common channels of these actions, and mayors in all types of cities experience violence and abuse. Nevertheless, mayors who are younger, female, in strong mayor systems, and in larger cities were more likely to be affected than their counterparts. Finally, with the exception of gender, the factors associated with greater likelihood of psychological abuse are not the same factors associated with experiences of physical violence.